The impact of outdoor walking interventions on frailty among older adults with mobility limitations: Findings from the Getting Older Adults Outdoors (GO-OUT) study - Tai-Te Su; Ruth Barclay; Rahim Moineddin; Nancy M. Salbach (PLoS ONE, 2025)
Objective Diverse strategies are needed to reduce frailty. This study evaluated the effects of two behavioural interventions targeting outdoor walking on reducing the level of frailty among community-dwelling older adults with mobility limitations. Methods Data from two participant cohorts of the Getting Older Adults Outdoors (GO-OUT) study were analyzed. After baseline evaluations, 190 participants were invited to a one-day educational workshop and were then randomized to either a 10-week supervised outdoor walk group (n = 98) or a 10-week telephone weekly reminders group (n = 92). Frailty was assessed using Fried’s frailty index at 0, 3, and 5.5 months. Mixed-effects linear and ordinal regression models were used to evaluate change in frailty score and phenotype over time after accounting for age, sex, study site, participation on own or with a partner, and cohort. Results At baseline, participant mean age was 74.5 ± 7.1 years; 73% were female, 7% were frail, and 59% were pre-frail. Total frailty scores decreased, on average, by 0.13 points ( b = –0.13, 95% CI: –0.26 to –0.01; p = .036) across all participants from 0 to 3 months (immediately post-intervention). Participants were 55% less likely to progress to more severe frailty phenotypes at 3 months compared to baseline (OR=0.45; 95% CI: 0.25 to 0.81; p = .008). No significant between-group differences or long-term effects were observed. Conclusions A short-term reduction in frailty was observed in older adults with mobility limitations following participation in behavioural interventions aimed at improving outdoor walking; neither intervention was superior. Supervised outdoor walk group and telephone weekly reminder interventions to increase outdoor walking may have the potential to mitigate frailty in older adults with mobility limitations.